2020
DOI: 10.48550/arxiv.2011.09466
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

On the Word Problem for Special Monoids

Abstract: A monoid is special if it admits a presentation in which all the defining relations are of the form w = 1. In this article, we study the word problem, in the sense of Duncan & Gilman, for special monoids, and relate the language-theoretic properties of this set to the word problem for the group of units of the monoid, by developing the theory of the words representing invertible words. We show that a special monoid has regular word problem if and only if it is a finite group. When C is a sufficiently restricti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…Thus we will speak of special inverse monoids and special monoids (and thereby implicitly assume that a presentation of the form given in (2.1) is simultaneously provided). The theory of special monoids is well-developed, originating in work by Adian [2] and Makanin [30,29,47], and developed further by Zhang [70,73,71,72] and Nyberg-Brodda [48], see also [45,Chapters 3 & 5]. Of particular importance for special monoids is the notion of the minimal invertible pieces of the presentation.…”
Section: Terminology and Definitionsmentioning
confidence: 99%
“…Thus we will speak of special inverse monoids and special monoids (and thereby implicitly assume that a presentation of the form given in (2.1) is simultaneously provided). The theory of special monoids is well-developed, originating in work by Adian [2] and Makanin [30,29,47], and developed further by Zhang [70,73,71,72] and Nyberg-Brodda [48], see also [45,Chapters 3 & 5]. Of particular importance for special monoids is the notion of the minimal invertible pieces of the presentation.…”
Section: Terminology and Definitionsmentioning
confidence: 99%
“…Inspired by this success, Duncan & Gilman [13, §5] introduced a generalisation of the word problem to finitely generated monoids. This generalisation is not a direct translation; indeed, the language of words equal to the identity element in a monoid is, generally speaking, completely insufficient to describe the structure of the monoid (for notable exceptions to this, see [40]). However, their generalisation, which we shall describe in §2, has the same language-theoretic properties as the original definition in the case that the monoid in question is a group; furthermore, its properties does not generally depend on the finite generating set chosen for the monoid.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the author has shown that the language-theoretic properties of the word problem of a finitely presented special monoid (cf. §2) are completely determined by its group of units [40]. Here the group of units of a monoid M is the maximal subgroup containing the identity element 1 of M .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations